Effect of reproductive and lifestyle factors on anti-mullerian hormone levels in women of Indian origin - Kaberi Banerjee; Amardeep Thind; Nisha Bhatnagar; Bhavana Singla; Kiran Agria; Payal Bajaj; Anshu Jindal; Sunita Arora; Poonam Goyal; Bhavana Mittal; Keshav Malhotra; Hrishikesh Pai; et al. (Wolters Kluwer Medknow Publications, 2022)
Background: Infertility is a world-wide problem and one third females. Over the years, anti-mullerian hormone (AMH) has emerged as a major marker of ovarian reserve. There is also increasing interest in determining the factors which can impact AMH levels. Aims: To correlate the association of reproductive and lifestyle factors on AMH levels in women of Indian origin. Settings and Design: Multicentric cross sectional study. Materials and Methods: The study was conducted using data extracted from the patient records of seven private fertility practices located in North India. Women who were attending these clinics for fertility treatment were requested to fill the questionnaire related to reproductive and lifestyle factors. Statistical Analysis used: Our outcome variable was level of AMH measured in the past 3 months, and was assessed as normal or low. All analyses were conducted using STATA 17. Results: We found a direct association of low AMH with increasing age, short cycles, amenorrhea and women with family history of premature menopause. We found a direct correlation of high AMH and women with polycystic ovary syndrome and those whose partners had Oligoasthenoteratozoospermia (OATS) or azoospermia. There was no correlation with smoking, sleep, diet, body mass index, cell phone or laptop use in our study. Conclusion: Reproductive and lifestyle factors may affect ovarian reserve and but there was a dearth of human studies in this area. To the best of our knowledge this is the first human study on the effect of AMH on Laptop and Cell phone use. We urgently need more studies to confirm or refute our findings so that we can counsel our patients well.